Tangled complicities and moral struggles: the Haushofers, father and son, and the spaces of Nazi geopolitics. (January 2015) - Barnes, Trevor J.; Abrahamsson, Christian
Abstract: Drawing on a biographical approach, the paper explores the tangled complicities and morally fraught relationship between the German father and son political geographers, Karl and Albrecht Haushofer, and the Nazi leadership. From the 1920s both Haushofers were influential within Nazism, although at different periods and under different circumstances. Karl Haushofer's complicity began in 1919 with his friendship with Rudolf Hess, an undergraduate student he taught political geography at the University of Munich. Hess introduced Haushofer to Adolf Hitler the following year. In 1924 Karl provided jail-house instruction in German geopolitical theory to both men while they served an eight-and-a-half month prison term for treason following the 'beer-hall putsch' of November 1923. Karl's prison lectures were significant because during that same period Hitler wrote Mein Kampf . In that tract, Hitler justifies German expansionism using Lebensraum, one of Haushofer's key ideas. It is here that there is a potential link between German geopolitics and the subsequent course of the Second World War. Albrecht Haushofer's complicity began in the 1930s when he started working as a diplomat for Joachim von Ribbentrop in a think-tank within the Nazi Foreign Ministry. He carried out several secret missions including negotiations with the Czech government over the Nazi annexation of Sudetenland. Karl's wife was Jewish, however, which according to Nazi Race Laws made Albrecht a Mischling [mixed-race]. Initially, Hess protected the family, but after he flew to Scotland in May 1941, circumstances became ever-more difficult for both Haushofers. Their tangled complicities and moral struggles were increasingly laboured and anguished, producing in the end tragic consequences. Highlights: Presents brief biographies of Karl and Albrecht Haushofer. Traces Karl and Albrecht Haushofer's relationship with those in Nazi high command including Adolf Hitler, Rudolf Hess and Joachim von Ribbentrop. Outlines the development and dissemination of Karl Haushofer's theory of geopolitics. Examines the work of Albrecht Haushofer in the Nazi diplomatic corps. Describes Albrecht Haushofer's participation in the German resistance movement.